Designing a Mobile Application to Assist Micro-Entrepreneurs in Understanding the Food Business Legality Process - Umami, Izzatul; Ahmad Naim Bin Che Pee; Hamzah Asyrani Bin Sulaiman; Ariy Khaerudin (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2023)
Micro-entrepreneurs are considered crucial by the government and stakeholders in economic development. However, the coaching and development opportunities for microenterprises have been limited, leading to a lack of technological advancements and self-competence among business actors. This research aims to address this gap by presenting the design and development of a mobile-based learning application called the Food Business System App (FBS App). The FBS App serves as a valuable resource for micro-entrepreneurs to acquire business knowledge related to government policies and enhance the value of their products. Developed using the Smart Apps Creator app on the Mobile App digital platform, the FBS App includes a collection of papers and videos covering various aspects of business and product legality. The learning content is divided into five parts: licensing, product branding, product manufacturing examples, and feedback. The FBS App is designed to minimize internet data usage, provide user-friendly experience, ensure fast technology access, and offer reliable technology performance for users with limited technological proficiency. The User-Centred System Design (UCSD) approach was employed in the application's design process, and the System Usability Scale (SUS) method was used for testing, resulting in a score of 77.2. It is anticipated that the FBS App will serve as a valuable reference tool for micro-entrepreneurs, enabling them to enhance the quality and competitiveness of their products.